ANALYSIS OF THE LEVEL OF COMMUNITY PREPAREDNESS FOR TSUNAMI DISASTER IN BENGKULU CITY - Zulfia Memi Mayasari; Yudhi Harini Bertham; Muchammad Farid; Arif Ismul Hadi (Universitas Sebelas Maret (UNS), 2026)
Geographically, Bengkulu City is located in a coastal area and is highly vulnerable to tsunamis. Since the earthquake and tsunami that hit the Indian Ocean in 2004, the attention of the Bengkulu City government to this phenomenon has increased significantly. However, to support government efforts in anticipating the risks and impacts of a tsunami, community preparedness is essential in addressing this threat. This study explores the level of community preparedness in facing the threat of tsunamis. A survey was conducted among a sample of 400 respondents from the coastal communities of Bengkulu City, spanning nine sub-districts, using a structured questionnaire. The questionnaire evaluated five parameters: knowledge and attitudes, family policies, emergency response plans, early warning systems, and resource mobilization. The level of community preparedness is determined using index analysis. The results show that the level of tsunami preparedness among the Bengkulu City community was at a moderate to ready level. The two sub-districts classified as being at the ready level are Gading Cempaka and Sungai Serut. In comparison, the seven sub-districts at the moderate level are Selebar, Teluk Segara, Muara Bangkahulu, Kampung Melayu, Ratu Agung, Ratu Samban, and Singaran Pati. Based on the results of this study, it is hoped that the government and the community can increase their preparedness for tsunami disasters to reduce the negative impacts that may occur.